2016
DOI: 10.18542/rebac.v2i1.804
|View full text |Cite
|
Sign up to set email alerts
|

A Formação De Classes De Equivalência via Pareamento Por Identidade E Discriminação Simples Com Conseqüências Específicas Para as Classes

Abstract: RESUMOO desempenho de participantes humanos freqüentemente mostra aprendizagem de relações não diretamente ensinadas após o treino de discriminações condicionais entre estímulos fisicamente diferentes. Essas relações emergentes documentam a formação de classes de equivalência. O presente estudo investigou se conseqüências específicas paras as classes (i.e., reforçadores específicos usados para cada classe potencial durante o treino) também integram as classes de equivalência. Vários estudos anteriores sugerira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
3
3
0
2
Order By: Relevance
“…Responding in these several types of MTS probes was consistent with the formation of three four-member equivalence classes (A1B1C1D1, A2B2C2D2, and A3B3C3D3). Specifically, positive results on tests of emergent conditional relations between written pseudo-sentences and abstract pictures (CD and DC), which were never presented together in training, support a transitive relation interpretation (e.g., if C1 discriminative and A1+B1 consequence relations and D1 discriminative and A1+B1 consequence relations, then C1D1 and D1C1 relations) and more generally equivalence class formation (Barros et al, 2006;Guld, 2005;Johnson et al, 2014;Pilgrim, 2020;Sidman, 2000;Yonkers, 2012). Notably, CD and DC tests were similar to those that were used in the seminal paper by Sidman (1971), which tested relations between two stimulus sets that were not directly related in training but related to a common auditory node.…”
Section: Testing For the Emergence Of Novel Relationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Responding in these several types of MTS probes was consistent with the formation of three four-member equivalence classes (A1B1C1D1, A2B2C2D2, and A3B3C3D3). Specifically, positive results on tests of emergent conditional relations between written pseudo-sentences and abstract pictures (CD and DC), which were never presented together in training, support a transitive relation interpretation (e.g., if C1 discriminative and A1+B1 consequence relations and D1 discriminative and A1+B1 consequence relations, then C1D1 and D1C1 relations) and more generally equivalence class formation (Barros et al, 2006;Guld, 2005;Johnson et al, 2014;Pilgrim, 2020;Sidman, 2000;Yonkers, 2012). Notably, CD and DC tests were similar to those that were used in the seminal paper by Sidman (1971), which tested relations between two stimulus sets that were not directly related in training but related to a common auditory node.…”
Section: Testing For the Emergence Of Novel Relationsmentioning
confidence: 98%
“…A pioneering study demonstrated stimulus class membership that was established by stimulusreinforcer relations (Dube, McIlvane, Mackay, & Stoddard, 1987). Positive results have been reported in other studies using class-specific consequences to establish different types of baseline relations that support the emergence of equivalence relations: identity matching (Barros, Lionello-DeNolf, Dube, & McIlvane, 2006;Dube & McIlvane, 1995;Schenk, 1994;Silveira, Mackay, & de Rose, 2018;Varella & de Souza, 2015), arbitrary matching (Dube et al, 1987;Dube, McIlvane, Maguire, Mackay, & Stoddard, 1989;Goyos, 2000;Guld, 2005;Luffman, 2012;Johnson, Meleshkevich, & Dube, 2014;Joseph, Overmier, & Thompson, 1997;Minster, Jones, Elliffe, & Muthukumaraswamy, 2006;Schenk, 1994;Varella & de Souza, 2014), and arbitrary constructed response MTS (Calado, Assis, Barboza, & Barros, 2018). Specific consequences 1 could optimize teaching, given the increase in the number of relations that are potentially established without direct training (Pilgrim, 2020;Varella & de Souza, 2015;Vladescu & Kodak, 2013), fostering the learning of untrained relations when target responses to a stimulus are followed by consequences with extra nontarget stimuli (Reichow & Wolery, 2011;Vladescu & Kodak, 2013).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…A partir destas afirmações sobre a formação de classes, os estudos se concentraram em avaliar duas características: 1) se os estímulos reforçadores utilizados no estabelecimento de uma discriminação condicional podem exercer função de modelo ou comparação da discriminação correspondente e 2) se treinos prévios com uso de reforços específicos podem fazer com que os elementos relacionados aos mesmos reforçadores sejam substituíveis entre si (Barros, Lionello-Denolf, Dube, McIlvane, 2006;Dube, McIlvane, Mackay & Stoddard;Dube, McIlvane, Maguire, Mackay, & Stooddard, 1989;Schenk, 1994;Dube & McIlvane, 1995;Pelick, 2005). Dube et al (1987) Dube et al (1987), as contingências do treino da identidade dos elementos X1 e X2 foram revertidas, de maneira que agora responder corretamente ao estímulo X1 produzia a consequência F2 e responder corretamente no X2 produzia F1.…”
Section: Formação De Classes De Equivalência E a Relação Resposta-refunclassified
“…Foi verificada, também, a possibilidade de formação de classes de equivalência como produto apenas de treinos de identidade com reforçamento específico (e.g. Barros, Lionello-DeNolf, Dube, & McIlvane, 2006;Dube & MacIlvane, 1995;Schenk, 1994, Experimento II). Estes dados corroboram a proposição de Sidman (2000) de que os elementos correlacionados com um mesmo reforçador passariam a compor uma classe de equivalência e que, quando utilizados reforçadores específicos, os reforçadores passariam a compor as classes de equivalência.…”
Section: Formação De Classes De Equivalência E a Relação Resposta-refunclassified